Case report of abdominal left upper quadrant collection secondary to fish bone perforation - Gheorghiu, Marcel Ioan; Bolliet, Marion; David, Patrice; Denis, Bernard (Medicine and Pharmacy Reports, 2020)
We present an unusual case of an intra-abdominal collection which evidenced a rare etiology and raises diagnostic particularities. Background. Fish bones ingestion is frequent, but seldom followed by complications. Those are often reported at specific sites. Objectives. This case report emphasizes the unusual presentation and site localization of a colonic perforation by a small fish bone, in the context of limited radiological accuracy at the diagnostic phase. Case presentation. A 37 year old male was admitted to the gastroenterology ward with upper and left sided abdominal pain associated with fever and marked fatigue. His medical history was marked by a sleeve gastrectomy in 2010 for obesity. Abdominal signs and elevated acute inflammatory syndrome on blood tests were followed by computer tomography which revealed a pericolic mass near the left splenic flexure. The pain and fever increased in intensity, so a laparotomy was proposed. Intraoperatively, a tumor-like lesion was found and a resection with oncologic limits was performed. Microscopic examination of the specimen revealed a fish bone, but only after surgery did the patient confirm that he had eaten fish meal the week before. The post-operative period was uneventful. Conclusion. Fish bones remain some of the most frequently ingested alimentary foreign bodies; they may cause atypical clinical presentations, frequently omitted by the patients themselves if symptoms appear delayed. They could also lead to possible high-risk complications which need to be addressed by surgeons.